(untitled) (Current Horticulture, 2024)
The experiment was conducted at College of Horticulture and Forestry, Rani Lakshmi Bai Central Agricultural University, Jhansi, during 2019-20 to see the effect of time of grafting and source of scion on grafting performance in guava (Psidium guajava L.). Treatments comprised four time of grafting, viz. T1: 1st fortnight of January, T2: 2nd fortnight of January, T3: 1st fortnight of February and T4: 2nd fortnight of February, and four different scion varieties viz. S1: Allahabad Safeda, S2: L-49, S3: Lalit and S4: Shweta. Significant differences of time of grafting and source of scion were observed in different grafting and growth parameters. The maximum bud sprouting (97.8%) was noted in T2S2, 2nd fortnight of January + L-49, which found at par with T4S1, 2nd fort night of February + Allahabad Safeda (95.6%), whereas minimum bud sprouting was noted in T1S4 1st fortnight of January + Shweta (53.3%). The highest final survival (95.6%) obtained from T2S2 (2nd fortnight of January + L-49) which was at par with T3S1 and T3S2, whereas lowest final survival was observed in 1st fortnight of January + Shweta (53.3%).